Modern methods of Ta₂O₅ coatings deposition for biomedical applications - Donkov, N.; Zykova, A.; Safonov, V.; Mateev, E. (Вопросы атомной науки и техники, 2009)
The study of e-beam evaporated Ta₂O₅ film structure and properties effect on cell/material response was performed. The surface properties and structure of e-beam evaporated Ta₂O₅ films were investigated by means of XPS and XRD methods. The cytotoxicity and cytocompatibility were estimated by in vitro tests. Films of Ta₂O₅ are bio- and chemically inert, which allows their use in various medical applications, e.g., in diagnostic and treatment techniques employing short-range quasi-static electric fields for stimulation of positive biological processes in live organisms. Дослідження структури та властивостей покриттiв Ta₂O₅, які нанесено методом електронно-променевого випарювання, було зроблено методами рентгеноструктурного аналізу та фотоелектронної спектроскопії. Цитотоксичнiсть i цiтосумiснiсть були визначені in vitro. Плiвки Ta₂O₅ мають бiо- та хімічно- інертні властивості, що сприятиме їх застосуванню з метою діагностики та лікування з використанням близькодіючих квазiстацiонарних електричних полів, якi стимулюють позитивні біологічні процеси. Исследования структуры и свойств покрытий Ta₂O₅, нанесенных методом электронно-лучевого испарения, были проведены методами рентгеноструктурного анализа и фотоэлектронной спектроскопии. Цитотоксичность и цитосовместимость были определены in vitro. Пленки Ta₂O₅ являются био- и химически- инертными, возможно их применение для диагностики и лечения с использованием близкодействующих квазистационарных электрических полей, стимулирующих позитивные биологические процессы.